Mongolian spots in GM1 gangliosidosis: a pictorial report. Issue 1 (January 2021) - Mishra, Shivani; Pai, Pranita; Uttarilli, Anusha; Girisha, Katta Mohan
Abstract : GM1 gangliosidosis is a lysosomal storage disorder, characterized by psychomotor deterioration, visceromegaly, facial coarseness, retinal cherry-red spots, and skeletal abnormalities. We report six unrelated patients with GM1 gangliosidosis with extensive Mongolian spots on the trunk and extremities that provided clue to clinical diagnosis. All patients exhibited psychomotor delay, coarse facies, hepatosplenomegaly, hypotonia, and dysostosis multiplex. Four patients had retinal cherry-red spots. The condition was confirmed by identification of very low activities of beta-galactosidase enzyme in peripheral leukocytes and biallelic pathogenic variants in the GLB1 gene. We identified one novel (c.1479G>T) and two known (c.75 + 2dup and c.1369C>T) pathogenic variants in homozygous state in them. Our work ascertains extensive Mongolian spots as a diagnostic handle for early recognition of GM1 gangliosidosis. Though a known feature of GM1 gangliosidosis, considerable variation in the prevalence and ethnic differences are observed. This report illustrates the Mongolian spots pictorially in Indian patients.